THE EFFECTIVENESS OF INTRADIALYSIS STATIC BIKE EXERCISE TOWARD FUNCTIONAL CAPACITY IN HEMODIALYSIS PATIENTS - Ria Desnita; Vivi Syofia Sapardi (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Patients with terminal renal failure require renal replacement therapy in the form of hemodialysis. Although already have hemodialysis therapy, there is still buildup of metabolic waste in patients’ body that results in a decrease in functional capacity. Decreased functional capacity in hemodialysis patients causes limitations in carrying out physical activities that reduces their quality of life. However, intradialysis physical exercise by using static bike can be a therapy to increase patients’ functional capacity.Objective: This study was aimed to determine the effectiveness of static bike exercise toward functional capacity in hemodialysis patients.Method: This research is a quantitative study with a quasi-experimental method using pre and post approach with control group design. Intervention and control groups were included in this study. There were 20 people in each group that were selected through consecutive sampling technique as samples of this study. The study was carried out in the hemodialysis room of RSUP Dr. M. Djamil, Padang.Result: The analysis was done using Paired T-Test with a degree of confidence of 95% and showed that intradialysis static bike exercise effectively increased the functional capacity in hemodialysis patients (p = 0.001).Conclusion: Intradialysis static bike exercise can be used as a nursing intervention to increase the functional capacity in hemodialysis patients. Key words: Hemodialysis, exercise, functional capacity.